2023
DOI: 10.3390/w15010181
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variation Characteristics of Precipitation in the Huaihe River Basin, China, as a Result of Climate Change

Abstract: Climate change is a global scientific problem, and its impact on the spatiotemporal variations of precipitation has been a crucial research topic. Although previous studies have used different methods to evaluate the precipitation characteristics of the Huaihe River Basin, the time series were short and the few stations could not fully and accurately represent the precipitation characteristics. In this study, daily temperature and precipitation data were collected from 233 meteorological stations in the Huaihe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…This pattern can be related to the ongoing consequences of climate change, including increased temperatures, changing air circulation patterns, and decreased soil moisture levels [31,40,41]. These factors are leading to changes in precipitation patterns and intensities, with wet regions becoming drier and dry regions becoming even more arid [42].…”
Section: Discussionmentioning
confidence: 99%
“…This pattern can be related to the ongoing consequences of climate change, including increased temperatures, changing air circulation patterns, and decreased soil moisture levels [31,40,41]. These factors are leading to changes in precipitation patterns and intensities, with wet regions becoming drier and dry regions becoming even more arid [42].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zheng and other scholars used DPSIR to construct an ecological environment indicator system to evaluate the status of ecological environment and resource development from 2005 to 2020, which provided decision makers with dynamic information about the development of ecological environment and resources. Boori, Mukesh Sing, and other scholars constructed the ecological vulnerability index of the Republic of Tatarstan using the DPSIR model, and the results showed that the human social ecological vulnerability is exacerbated by the increase in economic activities, which further emphasizes the importance of the DPSIR model in linking economic activities with environmental impacts [25]. These studies also emphasize the comprehensive, systematic, holistic, and flexible nature of the DPSIR model, which allows it to effectively integrate multiple considerations of resources, development, environment, and human health in order to reveal the causal relationship between the environment and the economy.…”
Section: The Dpsir Modelmentioning
confidence: 96%
“…Elevation is associated with the flow direction of surface water, and the recharge of groundwater to surface water, which can affect the spatial distribution of wetlands [45]. Slope is also an important factor of wetland distribution, as a steeper slope often represents a higher velocity and lower proportion of surface water [46]. The geomorphic type is the product of the combined action of exogenic force and endogenetic force, which determines the regional natural conditions and further affects the use of land and the distribution of wetlands [47].…”
Section: Impact Factor Of Wetland Changementioning
confidence: 99%